Analisis sistem bagi hasil muzara’ah dan Mukhabarah pada usahatani padi dan implikasinya terhadap kesejahteraan keluarga petani penggarap dan pemilik lahan di Kecamatan Praya Timur - Abdul Mutallib (Jurnal Ilmiah Mandala Education (JIME), 2015)
The purpose of this study is to investigate the implementation of the profit sharing system muzara’ah and mukhabarah on rice farming activity in terms of Islami persefektive and its implication toward the walfare of families of the sharecroppers and landowners in the district of East Praya Central Lombok. This is qualitative research whos primary data were  obtained by  direct  observation and  interviews while  the  secondary data  were obtained from the sub-district office in East Praya and institution assosiated with agriculture and other source.Analysis of the qualitative data was conduted inductively; a specific case or symptomis analysed and, later on, a more general conclusion are withdrawn.The  results  summarizes  the  implementation of  the  profit  sharing  system  of muzara’ah and mukhabarah on rice farming activity in East Praya district as follows: conceptually, the prsctice of nyakap in East Praya basically the same with the concept of Muzara’ah and Mukhabarah in Islam. The contract is simply oral. There are two kind of costs, namely, the overall cost of landowners (Muzara’ah) and the cost borne by thesharecroppers  (Mukhabarah).  Profit  sharing  is  carried  out  by  reducing  the  cost  inadvance. The allocation of these sharing for sharecroppers family is still for daily consumptiononly while for landowners, the allocation is more for future saving. In terms of walfare measurement, sharecroppers can only fulfill their basic needs while the owner of the land can do more to satisfy their living needs